2006
DOI: 10.1093/rheumatology/kel310
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillaroscopy is useful for the diagnosis and follow-up of autoimmune rheumatic diseases. A future tool for the analysis of microvascular heart involvement?

Abstract: Raynaud's phenomenon (RP) represents the most frequent clinical aspect of cardio/microvascular involvement and is a key feature of several autoimmune rheumatic diseases. Moreover, RP is associated in a statistically significant manner with many coronary diseases. In normal conditions or in primary RP (excluding during the cold-exposure test), the normal nailfold capillaroscopic pattern shows a regular disposition of the capillary loops along with the nailbed. On the contrary, in subjects suffering from seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 27 publications
2
130
0
6
Order By: Relevance
“…The nailfold of the second, third, fourth, and fifth finger was examined in each patient. According to Cutolo et al, the patterns identified within the SSc pattern included early, active, and late (11).…”
Section: Nailfold Videocapillaroscopy (Nvc)mentioning
confidence: 99%
“…The nailfold of the second, third, fourth, and fifth finger was examined in each patient. According to Cutolo et al, the patterns identified within the SSc pattern included early, active, and late (11).…”
Section: Nailfold Videocapillaroscopy (Nvc)mentioning
confidence: 99%
“…In normal conditions, the microvascular pattern is characterized by a regular array of microvessels with large intra/interindividual variability [19]. Usually, capillaries show a perpendicular disposition to the nailfold edge, with a capillary diameter lower than 20 μm, and at least 9 capillaries per linear millimeter are present.…”
Section: Normal Patternmentioning
confidence: 99%
“…Blood flow is also altered, with an average slowing of flow and increased periods of stasis [19]. Nagy et al found specific abnormalities in 87.5% of patients with diffuse and in 61.6% with limited form of SSc [5] by evaluating advanced capillary changes.…”
Section: Secondary Rpmentioning
confidence: 99%
See 1 more Smart Citation
“…Capillaroscopy is an non-invasive technique which allows in vivo investigation of the smallest blood vessels [8][9][10].…”
Section: Introductionmentioning
confidence: 99%